Visit-to-visit variability in LDL- and HDL-cholesterol is associated with adverse events after ST-segment elevation myocardial infarction: A 5-year follow-up study. (January 2016) - Boey, Elaine; Gay, Gibson Ming Wei; Poh, Kian-Keong; Yeo, Tiong-Cheng; Tan, Huay-Cheem; Lee, Chi-Hang
Abstract: Introduction: We evaluated the relationship between visit-to-visit low-density lipoprotein cholesterol (LDL-C) and high-density lipoprotein cholesterol (HDL-C) variability and 5-year clinical outcomes in patients who presented with ST-segment elevation myocardial infarction (STEMI). Methods: 130 patients presenting with STEMI and surviving to discharge were analyzed. Visit-to-visit LDL-C and HDL-C variability was evaluated from 2 months after discharge on the basis of corrected variation independent of mean (cVIM, primary measure), coefficient of variation and standard deviation. Major adverse cardiac event (MACE) included death, myocardial infarction, stroke, unplanned revascularization, and heart failure admission. Results: After an average of 62.4 ± 30.5 months follow-up, 41 patients (31.5%) had experienced MACE. Compared with the non-MACE group, the MACE group had a higher visit-to-visit LDL-C variability (cVIM: 0.23 ± 0.11 vs. 0.19 ± 0.08; p = 0.049; coefficient of variation: 0.24 ± 0.12 vs. 0.19 ± 0.00; p = 0.019; standard deviation: 24.1 ± 14.5 vs. 17.6 ± 10.0; p = 0.006), mean follow-up LDL-C (p = 0.033) and a higher prevalence of diabetes mellitus (p = 0.012). After adjusting for mean follow-up cholesterol levels and diabetes mellitus, each 0.01 cVIM increase in LDL-C and HDL-C variability increased the risk of MACE by 3.4% (HR: 1.034; 95% CI: 1.004 to 1.065; p = 0.025) and 6.8% (HR: 1.068; 95% CI: 1.003 to 1.137; p = 0.04), respectively. Results derived from coefficient of variation and standard deviation as measures of cholesterol variability were similar. Conclusion: This is the first report to show an independent association between visit-to-visit LDL-C and HDL-C variability and long-term MACE in patients presenting with STEMI. Highlights: High visit-to-visit cholesterol variability after a STEMI was associated with MACE. Known hyperlipidemia before STEMI was associated with lower LDL-C variability. Absence of lipid-lowering therapy on discharge predicts high HDL-C variability. Each 0.01 cVIM increase in LDL-C variability increased the risk of MACE by 3.4%. Each 0.01 cVIM increase in HDL-C variability increased the risk of MACE by 6.8%.